2007
DOI: 10.1002/ldr.771
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of land fragmentation on input use, crop yield and production efficiency in the mountains of Nepal

Abstract: Amidst the growing concern about agricultural underdevelopment in developing countries, this study addresses the causes and trends of land fragmentation. It analyses the impact of land fragmentation on input use efficiency, crop yield and production efficiency, especially with reference to a mountain district in Nepal. Necessary information was obtained from discussions with groups and individual land users and a questionnaire survey covering 184 households representing different degrees of land fragmentation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 13 publications
3
50
0
Order By: Relevance
“…Agrarian spatial planning includes the provision of the necessary infrastructure such as roads, irrigation systems, drainage systems, landscaping, environmental management, village renewal and soil conservation (Thomas, 2006a). LC aims to increase land-processing efficiency (Blaikie and Sadeque, 2000;Niroula and Thapa, 2007) and support rural development (Sklenicka, 2006). Thus, LC is very important for rural development.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…Agrarian spatial planning includes the provision of the necessary infrastructure such as roads, irrigation systems, drainage systems, landscaping, environmental management, village renewal and soil conservation (Thomas, 2006a). LC aims to increase land-processing efficiency (Blaikie and Sadeque, 2000;Niroula and Thapa, 2007) and support rural development (Sklenicka, 2006). Thus, LC is very important for rural development.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…Myyrä and Pietola (2002) found no connection between the average distance to field plots and farm profitability in Finland. Niroula and Thapa (2007) reported an association between smaller plots and higher yields. These conflicting results might reflect the complexity of the issue.…”
Section: Introductionmentioning
confidence: 97%
“…Although the strong general hypothesis is that the larger the plot size, the more efficient production will be, research results have been mixed. Decreasing agricultural productivity has been associated with the increasing distance (Bently, 1987;Najafi, 2000;Lerman, 2002;Vitikainen, 2004;Niroula and Thapa, 2007;Zhang and Wang, 2009;Falco et al,2010). An unfavourable field plot structure also reduces investments in land improvements (Mwakubo et al, 2005).On the other hand Wu et al demonstrated that the size of individual plots was not a significant factor for the productivity of grain production in China.…”
Section: Introductionmentioning
confidence: 99%
“…This trend has seriously threatened the sustainability of food security and livelihoods of millions of people who depend on agriculture. Land fragmentation not only deprives the land from proper care, but also weakens economic competitiveness of farmers through increased cost of labor and other inputs, leading to reduced net income (Blaikie and Brookfield, 1987;Paudel, 2001;Niroula and Thapa, 2007).…”
Section: Introductionmentioning
confidence: 98%